Utilization of the yard to support family food security in the pandemic time of Covid-19. Issue 4 (June 2021) - Edi, S
Abstract: This paper aims to provide and alternatives to the use of relatively narrow yards for cultivating hydroponic vegetables that are environmentally friendly and free from chemical pesticide residues. The activity was carried out in RT 9 Handil Jaya Village, Jelutung District, Jambi City during the Covid-19 pandemic from March to August 2020. Data collected has material requirements, production, distribution, and the impact of activities. The data were analysed quantitatively. The hydroponic technology of the Nutrient Film Technique system is placed attached to the yard fence using 12 rods of 3-inch pipe with a length of 3 m and a distance of 15 cm so that there are 240 planting holes using one reservoir. Several types of vegetables are planted, such as celery, lettuce, spinach, kale, pakcoy and kailan, which are planted as needed and harvest. The production of this vegetable has exceeded the needs of the family and even sold to markets, kebab and burger traders for 25, 000 IDR. Farming profit is 538, 703 IDR for every 40 days of harvest or 4, 309, 624 IDR in 8 harvests a year. Based on the calculation of B/C Ratio and R/C Ratio, this farming deserves to be continued and provides benefits.